Rethinking theory and practices in developing urban open spaces in Malaysia - Abdul Malek, Nurhayati; Mariapan, Manohar (2008)
Since the nineteenth century, the provision of parks has been a major focus in promoting places for relaxation and recreation. In other words, parks were designed to promote public health and to give some aesthetic value to an urban setting. Urban parks therefore can be regarded as open spaces, which cater to the needs of urban dwellers and the community as a whole. Here, urban open spaces are seen as the alternative venues for urban gateway. The fundamental focus of this paper is to provide an increasing understanding of the research, within the underlining value, belief, attitude and lifestyle of park user as well as to know how outdoor recreational activities in the Malaysian urban open space area are perceived. With urbanization and social demographic in mind, Malaysia has become an urban community which has led to realize the serious needs for urban open spaces. This paper will help to clarify the theory and literature part of the developing and managing process of urban open space which attempts to establish a deeper understanding on urban recreational spaces design and the experiences in the urban outdoor recreation.